Proposal of a short-form version of the Brazilian Food Insecurity Scale - Santos,Leonardo Pozza dos (2014)
OBJECTIVE To propose a short version of the Brazilian Food Insecurity Scale. METHODS Two samples were used to test the results obtained in the analyses in two distinct scenarios. One of the studies was composed of 230 low income families from Pelotas, RS, Southern Brazil, and the other was composed of 15,575 women, whose data were obtained from the 2006 National Survey on Demography and Health. Two models were tested, the first containing seven questions, and the second, the five questions that were considered the most relevant ones in the concordance analysis. The models were compared to the Brazilian Food Insecurity Scale, and the sensitivity, specificity and accuracy parameters were calculated, as well as the kappa agreement test. RESULTS Comparing the prevalence of food insecurity between the Brazilian Food Insecurity Scale and the two models, the differences were around 2 percentage points. In the sensitivity analysis, the short version of seven questions obtained 97.8% and 99.5% in the Pelotas sample and in the National Survey on Demography and Health sample, respectively, while specificity was 100% in both studies. The five-question model showed similar results (sensitivity of 95.7% and 99.5% in the Pelotas sample and in the National Survey on Demography and Health sample, respectively). In the Pelotas sample, the kappa test of the seven-question version totaled 97.0% and that of the five-question version, 95.0%. In the National Survey on Demography and Health sample, the two models presented a 99.0% kappa. CONCLUSIONS We suggest that the model with five questions should be used as the short version of the Brazilian Food Insecurity Scale, as its results were similar to the original scale with a lower number of questions. This version needs to be administered to other populations in Brazil in order to allow for the adequate assessment of the validity parameters.